2021
DOI: 10.1007/s00415-021-10783-4
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic and restorative therapies in neuromyelitis optica spectrum disorders

Abstract: Neuromyelitis optica spectrum disorders (NMOSD) are a group of autoimmune inflammatory conditions that primarily target the optic nerves, spinal cord, brainstem, and occasionally the cerebrum. NMOSD is characterized by recurrent attacks of visual, motor, and/or sensory dysfunction that often result in severe neurological deficits. In recent years, there has been a significant progress in relapse treatment and prevention but the residual disability per attack remains high. Although symptomatic and restorative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 139 publications
(189 reference statements)
0
12
0
1
Order By: Relevance
“…Unfortunately, as in the patient we reported, medication is often ineffective and has many side effects, such as dizziness, drowsiness, nausea, somnolence, and liver injury. [ 1 , 8 ] Nonpharmacological treatments for NMOSD-associated NP are being explored. Recently, a randomized controlled study showed that scrambler therapy can significantly alleviate NMOSD-associated NP, in which median NRS pain scores decreased from 5.0 to 1.5 within 10 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, as in the patient we reported, medication is often ineffective and has many side effects, such as dizziness, drowsiness, nausea, somnolence, and liver injury. [ 1 , 8 ] Nonpharmacological treatments for NMOSD-associated NP are being explored. Recently, a randomized controlled study showed that scrambler therapy can significantly alleviate NMOSD-associated NP, in which median NRS pain scores decreased from 5.0 to 1.5 within 10 days.…”
Section: Discussionmentioning
confidence: 99%
“…Neuromyelitis optica spectrum disorder (NMSOD) is an autoimmune disease of the central nervous system that causes multiple severe neurological deficits. [1][2][3] Neuropathic pain (NP), a common symptom of NMSOD, is often severe and intractable, [4][5][6] affecting more than 85% of patients, [5,7] and often resulting in a significant burden on the physical and mental health of patients, thus seriously reducing quality of life. [6,[8][9][10] At present, there is no standardized effective treatment for central NP caused by NMOSD.…”
Section: Introductionmentioning
confidence: 99%
“…53 Neuropathic pain usually requires combined medical and nonmedical treatment approaches that serve to reduce, but not eliminate, the pain, which may subside over time. 54 Similarly, muscle spasms in previously weakened muscles are common during recovery. Treatment with muscle relaxants may help but can exacerbate weakness.…”
Section: Key Pointsmentioning
confidence: 99%
“…Muscle relaxants are used to treat spasticity and anticholinergics to treat neurogenic bladder. 22 53 …”
Section: Treatment Considerationsmentioning
confidence: 99%
“…Muscle relaxants are used to treat spasticity and anticholinergics to treat neurogenic bladder. 22,53 Pediatric NMOSD In 1927, there was the first report of NMOSD in patients < 18 years old. It is possible that many cases described earlier were misdiagnosed as other demyelinating disorders, especially MS. 54 The International Pediatric Multiple Sclerosis Study Group (IPMSSG) published the pediatric diagnostic criteria for MS and related disorders in 2007 and revised them in 2013.…”
Section: Chronic Phase Treatmentmentioning
confidence: 99%